Social Media Analytics for K-State Admissions on Instagram and Twitter - Bratkiv, Devin T. (My University, 2018)
I have been in charge of running the social media accounts for K-State Admissions on Instagram and Twitter since July 2018. I would like to analyze the impact I have made on overall reach and engagement with the accounts by tracking audience, increase/ decrease in followers, amount of likes and retweets on various posts doing a semantic analysis as well by collecting comments and mentions. I would look at which posts do better than others and why, comparing buy-in with different types of content, as well as analyzing the impact time and day have on engagement. To get more diverse data, I would develop a comparison between the K-State Admissions accounts and two other competing accounts looking at schools in the Midwest and notable schools in the coastal regions to choose an adequate comparison. I would aim to present the data in a way that is easy to understand and adapt by others who follow me in this position.